2016
DOI: 10.1186/s12952-016-0050-3
|View full text |Cite
|
Sign up to set email alerts
|

Tlr2 deficiency does not limit the development of left ventricular hypertrophy in a model of transverse aortic constriction induced pressure overload

Abstract: BackgroundToll-like receptors (TLRs) are involved in a variety of cardiovascular disorders, including septic cardiomyopathy, ischemia/reperfusion, heart failure, and cardiac hypertrophy. Previous research revealed that TLR4 promotes cardiac hypertrophy in vivo. Therefore, we investigated whether TLR2 is also involved in the development of cardiac hypertrophy.MethodsTlr2 deficient and wild type mice were subjected to transverse aortic constriction (TAC) or sham operation procedure. Left ventricular, heart and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
1
8
1
Order By: Relevance
“…showed a lower heart weight in TLR2 −/− mice measured at 14 days and 28 days after TAC 12 . In contrast, another study found a higher heart weight in TLR2 −/− mice compared to WT at 14 and 28 days but no difference was detected in left ventricle weight between WT and TLR2 −/− mice 13 . We found in this study that hypertrophy, as evidenced by the increase in LV weight and mRNA levels of two hypertrophic markers ANP and BNP, occurred in both WT and TLR2 −/− mice to a similar extent from week 1 up to week 8 in response to sustained pressure overload (Fig.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…showed a lower heart weight in TLR2 −/− mice measured at 14 days and 28 days after TAC 12 . In contrast, another study found a higher heart weight in TLR2 −/− mice compared to WT at 14 and 28 days but no difference was detected in left ventricle weight between WT and TLR2 −/− mice 13 . We found in this study that hypertrophy, as evidenced by the increase in LV weight and mRNA levels of two hypertrophic markers ANP and BNP, occurred in both WT and TLR2 −/− mice to a similar extent from week 1 up to week 8 in response to sustained pressure overload (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…We and Bualeong et al . 13 achieved more severe aortic constriction using a 27 gauge needle, and both studies did not find a difference in left ventricular weight suggesting that the role of TLR2 probably depends on the severity of pressure overload. Furthermore, both studies found that lung weight after TAC did not differ between TLR2 −/− and WT mice.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…On similar lines, TLR2 deficiency reduces the severity of atherosclerosis in low-density lipoprotein receptordeficient mice (20). Contrast to these studies suggesting a detrimental role for TLR2 signalling in heart, few recent reports suggest that TLR2 deficiency exacerbates cardiac hypertrophy and remodelling after transverse aortic constriction in mice (12,21). Notably, TLR2 deficiency causes mature-onset obesity in mice and increases the susceptibility to high-fat dietinduced weight gain.…”
Section: Introductionmentioning
confidence: 97%